Understanding perceived value in tourism: Insights from destinations facing crises - Laurent Yacoub; Samer ElHajjar; Youssef Zgheib; Nada Jabbour Al Maalouf (PLoS ONE, 2025)
Tourism is a significant contributor to global economic growth, underscoring the importance of understanding visitors’ perceptions of attractions in destinations that face challenges and crises. This study investigates key factors influencing tourists’ perceived value of a destination, using the context of such challenging economic and political crises. It aims to determine how tourists evaluate their experiences in these destinations and how these perceptions affect their satisfaction and loyalty. By employing a quantitative method using a structured questionnaire distributed to 784 international tourists visiting Lebanon, the research measures perceived value and satisfaction, considering various destination attributes. The findings reveal that the inherent qualities of a destination significantly impact visitor evaluations, with value for money, competitive pricing, and high-quality experiences enhancing the likelihood of repeat visits and recommendations. Additionally, fun and family experiences play a crucial role in shaping perceived value. Contrary to expectations, knowledge and novelty do not significantly influence perceived value. This paper adds to the tourism literature by providing valuable insights into how tourists perceive value in crisis-prone destinations and addressing the resilience of the tourism sector in volatile regions which provides strategies for managers in such destinations. With its innovative approach, this study integrates quantitative analysis, highlighting the key factors that sustain tourists’ satisfaction and loyalty despite external obstacles.